Integrating Life Skills in Arabic Language Education: Enhancing Bilingual University Graduates’ Employability and Competencies - Nur Arifuddin; Dian Arsitades Wiranegara; A. Samsul Ma’arif; Mohammad Rifqi Junaidi; Bakri Muhammad Bakhiet (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2025)
Nowadays, in the competitive global job market, university graduates need more than language skills—they require essential life skills like communication, critical thinking, teamwork, and adaptability. This article presented the exploration of a life skills-based Arabic language education model at two Indonesian bilingual universities, UIN Malik Ibrahim Malang and UIN Sayyid Ali Rahmatullah Tulungagung. By integrating these skills into the Arabic curriculum, the model aimed to improve both language proficiency and employability. The qualitative method were used such as case studies, interviews, and classroom observations, the research identifies effective practices and challenges. Active learning approaches, including communicative and task-based methods, enhance student engagement and retention, while technology tools like e-learning platforms increase accessibility. However, challenges such as limited resources, faculty training, and cultural resistance remain. The study recommended strategic interventions for teacher training, curriculum reform, and international collaboration. It emphasized the relation between language learning and professional skills, advocating a holistic educational approach and suggesting future research on long-term employability and digital tools.